Perbaikan Tata Letak Produk Di Assalaam Hypermarket Dengan Metode Market Basket Analysis - Agestyana, Ajeng, Ir. Muchlison Anis, MT (2016)
Customer satisfaction is one of the purpose of retail industry. One of the factors affecting customer satisfaction is managing the product display. Display that draw up into the face of retail company itself. Assalaam Hypermarket is the company retail satisfaction that puts forward to consumers.Has an area of Assalaam Hypermarket at 4000 m2 cause problems of tired to consumers while searching for product who want to buy.But has an area, gap between the intended products by consumers quite far.this troubles that affected consumer decision to the coming back and expenditure, to stop the number of transactions was 1500 every day be 1300. The purpose of doing research is aware of product group and dominating sales to figure out how to design the layout according to consumers in spending habits. This research both market basket analysis (MBA). Information products dominated sales could be referred to know the habit of consumers in purchase. Custom referred to the product whatever bought consumers simultaneously. Apart from using mba also used activity relationship chart (ARC ) as tools to get results the layout according to consumers in spending habits and the government. The research result known that product groups that dominated sales is a snack modern, tissue, and cooking oil. With a value of support each of the 27,71 % , 26,45 % , and 26,20 %. While the purchase of products group toothpaste will affect the purchase group soap products worth 91,55 %. The couple adult milk products and perfume to be laid far apart because it was feared affect the quality of the product even though each mutual influential.